(untitled) (Bangladesh Journal of Botany, 2025)
Six antagonistic yeast isolates from different sources were tested for their resistance against Alternaria brassicicola under in vitro conditions. Saccharomyces cerevisiae isolates, namely, BK1 to BK7 inhibited the hyphal growth of pathogen in the range of 59.72 to 43.61 %, respectively. Out of 6 isolates BK 1 showed the best result against the tested pathogen. Bangladesh J. Bot. 54(1): 175-176, 2025 (March)